PERKEMBANGAN AGAMA ISLAM DI DESA SIPITUHUTA KECAMATAN POLLUNG KABUPATEN HUMBANG HASUNDUTAN (1966-2021) - Natal Sibarani; Lister Eva Simangunsong (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
This study aims to determine the development of the Islamic religion in Sipituhuta Village, Pollung District, Humbang Hasundutan Regency (1966-2021). In this study, the authors discuss starting from the background of the arrival of Islam, social interaction, and the development of Islam in Sipituhuta village. The research method used is the historical research method (historical). With field data collection techniques (Field research) and library research (library research). The results of this study indicate that the arrival of Islam in Sipitihuta village occurred during two phases. The interaction between Muslim and non-Muslim communities is very good. The development of the Islamic religion began in 1966-2021 seen from the number of people who adhered to it, worship facilities, and education. The stream of Islamic community organizations in Sipituhuta Village is NU (Nadlatul Ulama). As for evidence of Islamic heritage in Sipituhuta village, namely graves, mosques and prayer rooms, as a sign of the development of Islam in Sipituhuta Village, Pollung District, Humbang Hasundutan Regency. The development of Islam in Sipituhuta Village, Pollung District, Humbang Hasundutan Regency (1966–2021) concluded that Islam came to Sipituhuta Village during two phases (periods). The first phase of Islam entering Sipituhuta Village was brought by Oppung Raja Uli Lumban Gaol in 1930, when Oppung Raja Uli travelled to the city of Sibolga for his mistakes against the Dutch government during the establishment and construction of a church in Huta Godang. So that Oppung Raja Uli received a trial sentence to the top of the highest law in the city of Sibolga. And when there, Oppung Raja Uli Lumban Gaol was declared innocent and declared free after being freed. After being released, Oppung Raja Uli met with a Muslim resident employee who brought Raja Uli Lumban Gaol to his house, and there the resident officer made it clear that Oppung Raja Uli Lumban Gaol became a Muslim. After that, Oppung Raja Uli returned to his hometown, already a Muslim, and taught Islam to his own family. While the second phase of Islam entered Sipituhuta Village, it was brought by an Islamic religious figure from Sibulan-bulan named Tuan Ibrohim Sitompul in 1934, when Tuan Ibrohim Sitompul travelled to spread Islam to the Samosir area.